POLYMORPHISM OF INSULIN-LIKE GROWTH FACTOR-1 GENE AND ITS ASSOCIATION WITH GROWTH RATE IN DESI CHICKEN OF PAKISTAN - A. Ali; K. Javed; A. Ali; M. Akram; M. Dawood; A. H. Saleem (Journal of Animal and Plant Sciences, 2016)
The association of insulin-like growth factor-1 (IGF-1) polymorphism with growth trait was investigated in native Desi chicken of Pakistan. The present study was conducted at Animal Genetics Laboratory of Department of Livestock Production, UVAS Lahore. Fifty Desi chicken were procured from a conventional production farm situated in the vicinity of Ravi Campus for phenotypic and genotypic analysis. Genomic DNA was extracted from growing feather pulp using standard Phenol Chloroform Isoamylalcohol (PCI) method and the polymorphism of IGF-I gene was detected by PCR-RFLP-PstI. Both allelic and genotypic frequencies were calculated with the help of Pop gene 1.32 software. Statistical analysis of data was done using LSD (least significant difference) method as applied in the General Linear Model (GLM) procedure (SAS 9.1). Genotyping of birds revealed two alleles A (364 and 257 bp), B (621 bp) and three genotypes AA (6), AB (32), BB (12). AB genotype have the highest frequency of 64% while for BB and AA the frequencies are 24% and 12% among selected Desi Chicken. Analyzing different genotypes reveals that AA individuals had highest six month body weight (g) (1156.33±31.17) followed by (1112.16±21.04) and (904.08±31.08) of AB and BB genotypes respectively. Based on the results of this study, the application of IGF-1 locus in Marker Assisted Selection programs can be advised.
Keywords: IGF-1; Polymorphism; Body weight; Desi chicken; Pakistan